Comparative Genomic Analysis of Multi-Subunit Tethering Complexes Demonstrates an Ancient Pan-Eukaryotic Complement and Sculpting in Apicomplexa - Klinger, Christen M. (Public Library of Science, 2013)
Apicomplexa are obligate intracellular parasites that cause tremendous disease burden world-wide. They utilize a set of specialized secretory organelles in their invasive process that require delivery of components for their biogenesis and function, yet the precise mechanisms underpinning such processes remain unclear. One set of potentially important components is the multi-subunit tethering complexes (MTCs), factors increasingly implicated in all aspects of vesicle-target interactions. Prompted by the results of previous studies indicating a loss of membrane trafficking factors in Apicomplexa, we undertook a bioinformatic analysis of MTC conservation. Building on knowledge of the ancient presence of most MTC proteins, we demonstrate the near complete retention of MTCs in the newly available genomes for Guillardia theta and Bigelowiella natans . The latter is a key taxonomic sampling point as a basal sister taxa to the group including Apicomplexa. We also demonstrate an ancient origin of the CORVET complex subunits Vps8 and Vps3, as well as the TRAPPII subunit Tca17. Having established that the lineage leading to Apicomplexa did at one point possess the complete eukaryotic complement of MTC components, we undertook a deeper taxonomic investigation in twelve apicomplexan genomes. We observed excellent conservation of the VpsC core of the HOPS and CORVET complexes, as well as the core TRAPP subunits, but sparse conservation of TRAPPII, COG, Dsl1, and HOPS/CORVET-specific subunits. However, those subunits that we did identify appear to be expressed with similar patterns to the fully conserved MTC proteins, suggesting that they may function as minimal complexes or with analogous partners. Strikingly, we failed to identify any subunits of the exocyst complex in all twelve apicomplexan genomes, as well as the dinoflagellate Perkinsus marinus. Overall, we demonstrate reduction of MTCs in Apicomplexa and their ancestors, consistent with modification during, and possibly pre-dating, the move from free-living marine algae to deadly human parasites.